Labor outsourcing: the existential damage in outsourcing - Junior, Romeu Felix Menin (Revista Coleta Científica, 2019)
The theme of this article is: Labor outsourcing: The existential damage in outsourcing. The following problem was investigated: is there a current in Brazil that links outsourcing to existential damage? The following hypothesis was considered in view of the problem in question; how this helplessness is dealt with, the existential labor damage by doctrine and jurisprudence. The General Objective of this work is to gather an understanding always divided between doctrine and jurisprudence linking existential damage until outsourcing. The specific objectives are: To present and differentiate existential and moral damages; the relationship of the existential damage and the health of the worker and the ways of repairing the existential damage. This work is important in an individual and social perspective, because analyzing the scientific historical context, giving up guarantees, returns us to a situation analogous to the service borrower's dependence, suppressing rights and subjecting the worker to damage, depriving him of prospering by moving away that of fundamental rights, dreams, goals and objectives of life. This is a qualitative theoretical research lasting six months.